2017
DOI: 10.1175/jtech-d-16-0244.1
|View full text |Cite
|
Sign up to set email alerts
|

A Regime-Based Evaluation of TRMM Oceanic Precipitation Biases

Abstract: Over the tropical oceans, large discrepancies in TRMM passive and active microwave rainfall retrievals become apparent during El Niño–Southern Oscillation (ENSO) events. This manuscript describes the application of defined precipitation regimes to aid the validation of instantaneous rain rates from TRMM using the S-band radar located on the Kwajalein Atoll. Through the evaluation of multiple case studies, biases in rain-rate estimates from the TRMM radar (PR) and radiometer (TMI) are best explained when derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Roca et al () have shown that MCS of 12‐hr duration or longer bring 75% of tropical precipitation, and the subset of these systems traveling 250 km or more bring 60%. Several studies have compiled climatologies of tropical rainfall (Elsaesser & Kummerow, ; Houze et al, ; Zipser et al, ), and Henderson et al () have shown that organized precipitation causes much of the discrepancy between Tropical Rainfall Measuring Mission (TRMM) Microwave Imager (TMI) and precipitation radar (PR) retrievals during El Niño periods. They have also used TRMM data to show an increase in upper tropospheric (UT) moisture and stratiform rainfall during El Niño periods (Henderson et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Roca et al () have shown that MCS of 12‐hr duration or longer bring 75% of tropical precipitation, and the subset of these systems traveling 250 km or more bring 60%. Several studies have compiled climatologies of tropical rainfall (Elsaesser & Kummerow, ; Houze et al, ; Zipser et al, ), and Henderson et al () have shown that organized precipitation causes much of the discrepancy between Tropical Rainfall Measuring Mission (TRMM) Microwave Imager (TMI) and precipitation radar (PR) retrievals during El Niño periods. They have also used TRMM data to show an increase in upper tropospheric (UT) moisture and stratiform rainfall during El Niño periods (Henderson et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Different coefficients are then applied to retrieve precipitation rate as the former is a necessary input to the hydrometeor melting model [4,5]. For passive microwave (PMW) sensors such as the microwave imager (GMI) onboard the same GPM Core Observatory satellite, although precipitation type is not yet in its GPM-GMI Radiometer Precipitation Profiling (GPROF) product yet, some recent research indicate that pregrouping according to different weather systems or atmospheric stabilities (e.g., convective available potential energy, or CAPE) could potentially improve the precipitation rate retrieval [6,7].…”
Section: Introductionmentioning
confidence: 99%